2020
DOI: 10.3390/f11050539
|View full text |Cite
|
Sign up to set email alerts
|

What Is Threatening Forests in Protected Areas? A Global Assessment of Deforestation in Protected Areas, 2001–2018

Abstract: The protection of forests is crucial to providing important ecosystem services, such as supplying clean air and water, safeguarding critical habitats for biodiversity, and reducing global greenhouse gas emissions. Despite this importance, global forest loss has steadily increased in recent decades. Protected Areas (PAs) currently account for almost 15% of Earth’s terrestrial surface and protect 5% of global tree cover and were developed as a principal approach to limit the impact of anthropogenic activities on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 22 publications
0
32
1
Order By: Relevance
“…Our findings suggest that protected areas had lower rates of forest loss than non-protected areas; however, cumulative forest loss in protected areas still approached 20%, suggesting that protected area enforcement continues to be a major problem. Globally, Wade et al [28] estimated that between 2001 and 2019 there was an annual loss of approximately 0.2% per year of forest area within protected areas worldwide. In contrast, we estimate a forest-loss rate of 0.5% per year within protected areas from 1993 to 2017.…”
Section: Forest Loss In Protected Areas and Community Forestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that protected areas had lower rates of forest loss than non-protected areas; however, cumulative forest loss in protected areas still approached 20%, suggesting that protected area enforcement continues to be a major problem. Globally, Wade et al [28] estimated that between 2001 and 2019 there was an annual loss of approximately 0.2% per year of forest area within protected areas worldwide. In contrast, we estimate a forest-loss rate of 0.5% per year within protected areas from 1993 to 2017.…”
Section: Forest Loss In Protected Areas and Community Forestsmentioning
confidence: 99%
“…In contrast, we estimate a forest-loss rate of 0.5% per year within protected areas from 1993 to 2017. Wade et al [28] found Cambodia and Côte d'Ivoire to be the two tropical countries with the highest rate of forest loss within protected areas in the world. In our study, the largest forest losses from protected areas occurred in 2004 and 2010.…”
Section: Forest Loss In Protected Areas and Community Forestsmentioning
confidence: 99%
“…Therefore, knowing how forest covers change over time inside and outside protected areas, especially in inaccessible locations, can improve forest conservation and management [9,55,57]. Information on forest fires, timber harvesting, and other anthropogenic activities around reserves, along with the help of remote-sensing techniques, can support park protection [9,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these are areas of high environmental stress and represent possible threats to the resilience of the landscape, as they can affect the self-organisation of the system. Anthropogenic activities related to the removal of natural vegetation, as well as extensive and intensive land use conversion [ 11 14 ], are responsible for the increase in landscape fragmentation and expansion of their transition zones. Habitat fragmentation is a major threat to landscape connectivity [ 15 ] and contributes a large human footprint in the Anthropocene, especially in tropical forests [ 16 ].…”
Section: Introductionmentioning
confidence: 99%